Human Rights, Islamophobia, and the War on Terrorism - Aidir Amin Daud (Hasanuddin Law Review, 2021)
Declaration of Human Rights is one of the universal law products, which has become an agreement for the civilization of nations. Hence, everyone has the right to recognition everywhere as a person before the law. One of the substances of Human Rights principles is not to allow the growth of repressive attitudes from all elements in society. Including the attitude and role of the media as the guardian of human rights. This study analyzes the role of media in the production process of anti-Muslim frames, contributing to the growth of islamophobia, thereby supporting the government's repressive efforts and ignoring human rights principles. This study is a qualitative study related to the trends and challenges of islamophobia and the war on terrorism from a global perspective. The results show that islamophobia has led to the Muslim community's discrimination, exclusion, and acceptance of prejudice. This activity creates a scourge for decision-makers in many countries with numerous attributes associated with its growth. The originality of this paper exhibits a comprehensive investigation of islamophobia, international law, and terrorism. The result also showed that the media tend to discriminate due to fanaticism, violence, and terror in many extreme religious groups, thereby encouraging the spread of islamophobia.